2008
DOI: 10.1109/tns.2008.2001834
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Resistant Erbium-Doped Fiber for Spacecraft Applications

Abstract: Radiation-induced absorption and lasing efficiency of a hermetically coated erbium-doped fiber saturated with molecular hydrogen are studied. It is shown that H 2 -loading of hermetically coated erbium-doped fibers prolongs their service time in space more than in 5 times, making such fibers promising for space applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…By changing the fabrication process, another group of researchers showed that it is possible to avoid the Al codoping, improving the radiation resistance of erbium-doped optical fibers [7]. A last technique working for both phosphosilicate or aluminosilicate optical fibers is the loading of the fiber core and cladding with hydrogen (or deuterium); in this case, it has been shown that the amplifier radiation response is greatly improved but the positive impact of the treatment remains time-dependent and not really adapted in its current forms to long term space missions [6,11,12]. …”
Section: Context Of Our Workmentioning
confidence: 99%
“…By changing the fabrication process, another group of researchers showed that it is possible to avoid the Al codoping, improving the radiation resistance of erbium-doped optical fibers [7]. A last technique working for both phosphosilicate or aluminosilicate optical fibers is the loading of the fiber core and cladding with hydrogen (or deuterium); in this case, it has been shown that the amplifier radiation response is greatly improved but the positive impact of the treatment remains time-dependent and not really adapted in its current forms to long term space missions [6,11,12]. …”
Section: Context Of Our Workmentioning
confidence: 99%
“…Many researchers have demonstrated that H 2 -loading is beneficial for improving the radiation resistance of fibers [ 13 , 14 ], but there are some limitations as well. For example, H 2 molecules can easily escape, the mechanical strength of the coating may decrease, and H 2 causes additional absorption [ 15 ]. Even worse, owing to the reducing environment caused by H 2 , Yb 3+ ions are easily reduced into Yb 2+ ions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have then been applied to enhance the fiber radiation resistance such as codoping the fiber core with cerium [ 8 ] or loading the fiber with H 2 or D 2 gas. [ 9 ] These hardening techniques at the material levels are based on the passivation of the Al‐related defects by the H 2 or D 2 gas or on favoring the competition between radiation‐induced defects to lower the RIA at the operating wavelengths. It is also possible to improve the radiation tolerance acting at the component level with appropriate fiber designs.…”
Section: Introductionmentioning
confidence: 99%